New Optimization Algorithms and their Applications : Atom-Based, Ecosystem-Based and Economics-Based - Zhao, Weiguo, author 651358; Wang, Liying, author 651359; Zhang, Zhenxing, author 651360; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2021)
New Optimization Algorithms and Applications: Atom-Based, Ecosystem-Based and Economics-Based presents the development of three new optimization algorithms - an Atom Search Optimization (ASO) algorithm, an Artificial Ecosystem-Based Optimization algorithm (AEO), a Supply Demand Based Optimization (SDO), and their applications within engineering. These algorithms are based on benchmark functions and typical engineering cases. The book describes the algorithms in detail and demonstrates how to use them in engineering. The title verifies the performance of the algorithms presented, simulation results are given, and MATLAB® codes are provided for the methods described.